Advanced BlackBerry 6 development - King, Chris, 1972- (Apress ; Distributed to the Book trade worldwide by Springer Science+Business Media, 2011)
Looks at the features included with SDK6, introduces cross-platform libraries, discusses the BlackBerry's multimedia capabilities, and includes lessons on building applications.